Ecology of mangrove patches in the vembanad lake at Panangad - Sukam Monalisha devi (Department of Fishery Hydrography, College of Fisheries, 2009)
The present study was carried out in mangrove area and backwater connected to the backwater through a sluice gate where mangrove patches are present. The study was undertaken in order to identify the floral composition, fishes, prawns, crabs and molluscs found in the area. The seasonal changes of hydrographical parameters like DO, pH, water temperature, alkalinity, salinity, primary productivity, silicate-silicon, phosphate-phosphorus, nitrite-nitrogen and nitrate-nitrogen and the sediment characteristics like sediment pH, total organic carbon, sediment texture were also studied. The mangrove species found in the study area were identified. Water temperature was minimum during south-west monsoon and maximum was during pre-monsoon. Average water temperature was lesser in mangrove area. Negative correlation was found between dissolved oxygen and all the nutrients. Through out the study period pH was alkaline. pH increased with increase in salinity and alkalinity. Dissolved oxygen was high during monsoon when compared with pre-monsoon period. It decreased with increased in salinity. Maximum salinity recorded during pre-monsoon when there was less freshwater intrusion. Average salinity was higher in backwater. Salinity showed negative correlation with all the nutrients. Alkalinity minimum value was observed during south-west monsoon it increases in post-monsoon and attained maximum during pre-monsoon. Alkalinity is higher in mangrove area. Primary productivity was maximum when light intensity was maximum. Average concentration of nutrients was higher in mangrove area. Maximum concentration was seen when inflow of freshwater was more. Sediment pH was minimum during pre-monsoon. Average sediment pH was lower in mangrove area than to backwater. Average Total organic carbon was maximum during post-monsoon in mangrove area and backwater. Sediment texture showed that substratum was silty sand in both the stations. When sand percentage increased total organic carbon was lowered. t-Test was done to compare significant difference between mangrove area and backwater. It showed that there was no significant difference with any of the hydrographical parameters between the two stations except primary productivity. ANOVA was conducted separately for two stations to compare significant difference between three seasons- monsoon, post-monsoon and pre-monsoon. In mangrove area pH and dissolved oxygen did not showed significant seasonal difference. In backwater water temperature, phosphate and nitrite did not show any seasonal difference. Dominant mangrove plants include Rhizophora mucronata, Brugiuera gymnorhiza, Brugiuera cylindrica, Avicennia officinalis, Acrostichum aureum, Acanthus ilicifolius. Prawns and crabs were abundant. Among prawns Fenneropenaeus indicus was caught through out the study period. Among crabs Scylla serrata and Uca spp. were commonly found. Balanus, Lamellidens sp., Villorita sp. were also seen in the study area. 30 species of fishes were identified from the study area and major contribution was by fishes belonging to the Order Perciformes. Mostly juveniles contributed to the fish catch.